Does online technology provide sustainable HE or aggravate diploma disease? Evidence from Bangladesh—a comparison of conditions before and during COVID-19 - Alam, Gazi Mahabubul (Elsevier, 2021)
Higher education (HE) serves to produce well trained and job-ready graduates. Despite this belief, whether HE produces certificates/qualifications or job-ready graduates—this debate remains unsettled. To date, the current COVID-19 pandemic which erupted in late 2019 continues to create much economic, social and political dislocation throughout the world. Consequently, one outcome for HE during this crisis is the much greater dependence on online/digital technology to deliver courses and programs. Although it is not considered to be a complete substitute, critics argue that education delivered through online technology has expended the ‘diploma disease’ crisis and subsequently may pose a threat to the viability of producing HE graduates. It has been suggested that this can result in significant long-term problems that may be impossible to recover from. This study was based on a ‘empirical survey’ where the sample incorporated 240 people in two groups (before and during COVID-19, for a total of 120 in each), and the objective was to examine academic and job-readiness of graduates in greater depth. Findings demonstrate that pre-pandemic students scored poorly academically compared to their post-pandemic classmates. Pre-pandemic graduates, on the other hand, had higher work readiness scores in terms of both aptitude and practical aspects. Furthermore, both groups outperformed their job-readiness scores in terms of learning performance. This raises the question: is it the job of higher education to promote sustainable production of graduates or deliver certificates and degrees? COVID-19 appears to have been utilised by the HE system as an excuse to exacerbate the “diploma disease crisis,” a scenario that must be resolved by developing a proper policy framework that allows HE to play the necessary role in an emergency. Meaningful measures should be taken so that online technology is employed properly in this situation.